Vermicompost application improves leaf physiological activity, 2-acetyl-1-pyrroline, and grain yield of fragrant rice through efficient nitrogen assimilation under Cd stress - Iqbal, Anas; Chen, Xiaoyuan; Khan, Rayyan; Zaman, Maid; Khan, Aamir Hamid; Kiedrzyński, Marcin; Ebaid, Mohamed; Alrefaei, Abdulwahed Fahad; Lamlom, Sobhi F.; Tang, Xiangru; Zeeshan, Muhammad (Frontiers in Plant Science, 2024)
Cadmium (Cd) pollution in arable soils and its accumulation in rice plants have become a global concern because of their harmful effects on crop yield and human health. The in-situ stabilization method which involves the application of organic amendments such as vermicompost (VC), is frequently utilized for the remediation of Cd-contaminated soils. This study investigated the effects of VC on the soil chemical properties and the physio-biochemical functions of fragrant rice, as well as nitrogen (N) metabolism and assimilatory enzyme activities, 2-acetyl-1-pyrroline (2AP) content in rice grains, and the grain yields of fragrant rice cultivars, i.e., Xiangyaxiangzhan (XGZ) and.Meixiangzhan-2 (MXZ-2) under Cd stress condition. Four doses of VC (.VC1 = 0, VC2 = 3 t. ha-1, VC3 = 4 t ha-1, and VC4 = 6 t ha-1) and two levels of Cd (0 and 25 mg Cd kg-1) were used in this study. Our results showed that VC supplementation significantly (p < 0.05) improved soil characteristics, including soil organic carbon, available N, total N, phosphorus (P), and potassium (K). Furthermore, VC enhanced plant physiological and biochemical attributes in fragrant rice, such as net photosynthetic rate (Pn), nitrate reductase (NR), nitrite reductase (NiR), glutamine synthetase (GS), glutamate oxoglutarate aminotransferase (GOGAT) enzyme activities, protein contents, amino acid, and 2-acetyl-1-pyrroline (2AP) contents under Cd stress condition. Specifically, the VC-amended treatment, Cd2 + VC3, led to an 86.75% increase in Pn and 2AP, and a 60.05% and 77.55% increase in grain yield for MXZ-2 and XGZ cultivars, respectively, compared to Cd-only treated plants (Cd2 + VC1). In addition, VC application significantly (p < 0.05) decreased the Cd uptake and accumulation in rice plants. The correlation analysis indicated that leaf physiological activity and biochemical traits are strongly correlated with soil qualitative traits, suggesting that improved soil health leads to enhanced leaf physiological activity, N metabolism, grain 2AP content, and grain yields. Among the treatments, Cd2 + VC3 showed the best performance in terms of soil fertility and rice quality and production. Consequently, our study indicates that using VC in soils may benefit rice growers by improving soil fertility and supporting sustainable rice productivity and quality in soils contaminated with Cd.